Hypertension Drug Sales Pattern in Yogyakarta Through the Tokopedia Platform - Piter, Sarah Jesika; Soegiantoro, Didiek Hardiyanto; Kurniawati, Aloysia Yossy; Kristiyani, Ani (Sean Institute, 2025)
Hypertension is a chronic disease with a high prevalence in Indonesia, including the Special Region of Yogyakarta (DIY), so the availability of antihypertensive drugs is crucial. This study aims to examine the sales patterns of antihypertensive drugs through the Tokopedia e-commerce platform in DIY, with a focus on variations in sales volume and types of drugs based on administrative regions and pharmacotherapy classifications. The method used was descriptive quantitative with direct observation on Tokopedia on April 29, 2025, covering five districts/cities: Yogyakarta, Sleman, Bantul, Kulon Progo, and Gunungkidul. The results showed that Sleman Regency recorded 140 boxes and Yogyakarta City recorded the highest sales of 262 boxes, while Bantul recorded 29 boxes and Gunung Kidul 2 boxes while Kulon Progo recorded no sales at all. Generic drugs dominated the sales, especially Calcium Channel Blockers (CCB) with 201 boxes and Angiotensin Receptor Blockers (ARB) with 99 boxes. Meanwhile, branded drugs were mostly found in the ACE Inhibitor group, although in total this group recorded the least number of sales. The conclusions indicate inequality in e-commerce distribution and utilization between districts/cities, as well as public preference for more affordable drugs. Therefore, strategies to equalize access and educate the use of e-commerce in drug distribution are needed, in order to support the equitable and efficient management of hypertension.